DAMPAK MEDIA SOSIAL TERHADAP PROMOSI SIWANG PARADISE DI KOTA AMBON - Amelia Tahitu; Demsy Wattimena (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
The research aims to determine and analyze the impact of social media on the promotion of Siwang Paradise in Ambon City. In this study, the data collection technique used was a questionnaire (questionnaire), observation and interviews. instagram, and youtube, with measuring indicators namely; the type of information, the number of posts (updates), the number of followers, and account users have a significant influence on Siwang Paradise tourism promotion in Ambon City. This is based on the t test which means the hypothesis is accepted, based on the value determination test (r2) showing that 66.7% of the influence of Siwang Paradise tourism promotion (Y) is influenced by social media (X). while the remaining 33.3% is influenced by other factors not examined in this study, variable Y, namely Siwang Paradise tourism promotion with indicators, Namely; natural conditions, clean & cool air, beautiful environment, natural spots, photo spots, and culinary spots have a significant effect on variable X, so that the hypothesis results are accepted.